POTENSI LIMBAH INDUSTRI PERTANIAN DI P3G PERTANIAN JANGARI, CIANJUR STUDI KASUS: PEMANFAATAN LIMBAH KEPALA IKAN PAT IN (PANGASIUS PANGASIUS) - Lisyastuti, Esi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
This article discusses the potency waste fisheries industry in case studyP3G Jangari Cianjur as an effort of increasing added value of fillet wasteof Pangasius pangasius. One of the alternative technique is driedhypophyses (pituitary glands). The dried hypophyses can be producedfrom fillet waste of Pangasius pangasius. Hypophyses should be collectedfrom mature, freshly killed Pangasius. They should then be dehydratedand stored. These dried hypophyses will be needed for the preparation ofthe hormonal extract to be injected into the Pangasius breeders forinducing their maturation.